Shear Strength of Reinforced High-Performance Concrete Wide Beams - BARZAN OMAR MAWLOOD; AHMED HEIDAYET MOHAMMAD; NAWAL M. ABDULRAZZAQ; KAMARAN S. ISMAIL (Zanco Journal of Pure and Applied Sciences, 2021)
Wide shallow beams have become more common among structural designers since having more space for utility services under the floor. However, the provisions of codes of practice need to be evaluated against an experimental data to evaluate their margin of safety for this type of structural element. This paper is an experimental and theoretical investigations on the shear behavior and capacity of wide shallow beams. A total of seven beam specimens were tested to assess the effect of beam width to height ratio (b/h) which ranged from 0.67 to 3; shear reinforcement ratio ranging from 0 to 0.222%; and carbon fiber content ranging from 0 to 0.53%. The results show that with increasing width to height ratio, the shear strength of the beam decreased and the provisions of codes of practice (ACI318-14 and EC2) might not lead to accurate results when they are used to predict the shear capacity of wide shallow beams.